2013
DOI: 10.1017/s1366728913000400
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive shift in the bilingual mind: Spatial concepts in Korean–English bilinguals

Abstract: Recent research shows that speakers with different first languages perceive various cognitive domains in different ways and that bilinguals’ conceptualization patterns are affected by the concepts of both languages. The present study extends Choi and Bowerman (1991) by examining the categorizations of spatial concepts in adult Korean–English bilinguals. Using similarity judgments, the study compares the conceptualization patterns of “put in” and “put on” by Korean–English bilinguals and Korean and English mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
50
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 50 publications
4
50
2
1
Order By: Relevance
“…Athanasopoulos, et al, 2011;Bylund et al, 2013;Kurinski and Sera, 2011;Miles et al, 2011) have shown that acquisition of construal modes demonstrate developmental patterns across groups of learners with different levels of bilingualism. The findings from the present study provide evidence that while the performance of low-level bilinguals approximated that of the monolinguals, the performance of high-level bilinguals diverged significantly from both groups, suggesting that acquiring English has led to cognitive restructuring (Athanasopoulos, 2011;Park and Ziegler, 2014). While monolinguals and low-level bilinguals were found to construe actions in relatively high levels, high-level bilinguals showed significantly lower level action construals.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Athanasopoulos, et al, 2011;Bylund et al, 2013;Kurinski and Sera, 2011;Miles et al, 2011) have shown that acquisition of construal modes demonstrate developmental patterns across groups of learners with different levels of bilingualism. The findings from the present study provide evidence that while the performance of low-level bilinguals approximated that of the monolinguals, the performance of high-level bilinguals diverged significantly from both groups, suggesting that acquiring English has led to cognitive restructuring (Athanasopoulos, 2011;Park and Ziegler, 2014). While monolinguals and low-level bilinguals were found to construe actions in relatively high levels, high-level bilinguals showed significantly lower level action construals.…”
Section: Discussionmentioning
confidence: 47%
“…For instance, Park and Ziegler (2014) showed that the following classification patterns emerged as bilingual participants categorized spatial motions: creating a new unitary category distinct from the monolingual group, combining characteristics of both language-specific semantic distinctions to form a hybrid, showing an inbetween performance, and patterning with either L1-based or L2-based concepts. These results indicate that bilingualism may result in the adjustment of bilinguals' sensitivity to their native language construal patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the present study, learning English as a foreign language can be considered to be the factor which influenced the cognitive processing of the high-level learners so that they developed a marked tendency to construe different phenomena in a lower level, which in turn lead to significantly lower estimated temporal and spatial distance. The findings contribute to the growing body of research on the language-thought interaction in various perceptual domains (Elston-Guttler & Williams, 2008;Kurinski & Sera, 2011;Park & Ziegler, 2014) by suggesting that learning a new language can have a significant impact on the cognitive behaviour of bilinguals.…”
Section: Discussionmentioning
confidence: 55%
“…Findings from the research on the language-thought interface suggest that the maintenance of language-specific cognitive processing of L2 learners is influenced by a number of factors such as frequency of language use (Park & Ziegler, 2014), language proficiency (Athanasopoulos, 2007(Athanasopoulos, , 2009Park & Ziegler, 2014), age of acquisition onset , and length of cultural immersion (Boroditsky, 2001;Cook et al, 2006;Athanasopoulos, 2007;Athanasopoulos et al, 2010;, language of instruction (Athanasopoulos, 2007). For example, Bylund et al (2013) tested whether the speakers of Afrikaans (a non-aspect language) tended to encode event endpoints more than the Afrikaans L2 learners of English (an aspect language).…”
Section: Discussionmentioning
confidence: 99%